Effectiveness of setter ability in the provincial sports week championship in 2022 - Fizariani, Deatri; Supriatna, Eka; Rubiyatno, Rubiyatno (Universitas Suryakancana, 2023)
This study aims to determine the effectiveness of the setter's ability at the 2022 volleyball championship. This study used a quantitative approach with survey methods by technically observing ongoing matches. The research sample was the setters consisting of the best teams who made it to the top 8, semifinals and finals, using a purposive sampling technique. The data collection technique was a direct observation of the playing field and was assisted by video documentation on the success, rally and failure of a setter passing the ball at the 2022 Provincial Sports Week Championship. It was assessed based on the observation sheet. The research results indicate that the average setter effectiveness in the top 8 matches was 34% in the very ineffective category. The average result of the effectiveness of the setter in the semifinal match was 48% in the ineffective category. The average result of the effectiveness of setters in the final match was 51% in the ineffective category. The conclusion is that the average effectiveness of the setter's abilities in the Provincial Sports Week Championship from the Big 8 match stage to the final setter is ineffective in feeding the ball.Keywords:Â Effectiveness, Ability, Setter